2015
DOI: 10.1002/ejoc.201500874
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Binding of Sugar Receptors (Lectins) to a Synthetic Tricyclic Tn Mimetic and Its Glycopeptide Version

Abstract: Cycloadduct 1 is a conformationally constrained mimetic of the tumor‐associated Tn antigen. It maintains the 4C1 conformation and the α‐O‐glycosidic linkage of the natural epitopes. Due to its tricyclic structure, the anomeric linkage is constrained and its conformation “frozen”. Using saturation transfer difference NMR spectroscopy experiments, epitope mapping for binding by three lectins [i.e., from Erythrina cristagalli (ECL), human macrophages (MGL), and from Helix pomatia (HPA)] was carried out. Striking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Based on the structure of the previously synthesized sialo‐derivative 1 (Figure 1a), [18–20] the synthesis of 2 has been conceived. The sialo‐derivative 2 (Figure 1a), having a similar scaffold than 1 but bearing a biphenyl substituent at position 9, was synthetized based on the observation that a similar sialo‐analogue increased the bound potency and selectivity for CD22 [21] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the structure of the previously synthesized sialo‐derivative 1 (Figure 1a), [18–20] the synthesis of 2 has been conceived. The sialo‐derivative 2 (Figure 1a), having a similar scaffold than 1 but bearing a biphenyl substituent at position 9, was synthetized based on the observation that a similar sialo‐analogue increased the bound potency and selectivity for CD22 [21] …”
Section: Resultsmentioning
confidence: 99%
“…Overall, our structural and affinity data showed that the sialyl derivative 1 can strongly interact with h‐CD22; thus, a class of related compounds may be designed as promising candidate for glycoimmunotherapy targeting CD22. Furthermore, the functionalization and characterization of suitable nanomaterials coated with 1 ‐like ligands may lead to interesting therapeutic applications, for example to efficiently probe the cell surfaces [13–33] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of these evidences, the aim of the present study was to investigate the activity of the fully synthetic antigen 1 [37,38] (Fig. 1) on iNKT and NK cell activation.…”
Section: Introductionmentioning
confidence: 99%